2018
DOI: 10.1177/2516600x18816204
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Engineering, Knowledge Management, and Product Innovation

Abstract: Evidence has shown that organizations seldom achieve the advantages offered by concurrent engineering (CE) practices. This may be attributed to the fact that the concept of CE is vague in terms of core elements and needs further investigation. In addition, despite the importance of CE and knowledge management in the context of product innovation, empirical investigation in this area is lacking. To this end, the goal of this research is to identify the critical dimensions of CE and empirically investigate the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 136 publications
(173 reference statements)
1
12
0
Order By: Relevance
“…In addition, the staff were able to concentrate on planning the implementation test. These findings coincide with some authors [32,48,51,52], who indicated that the early disclosure of information reduces uncertainty and promotes the detection of problems within the system.…”
Section: Product Development Planning and Documentationsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the staff were able to concentrate on planning the implementation test. These findings coincide with some authors [32,48,51,52], who indicated that the early disclosure of information reduces uncertainty and promotes the detection of problems within the system.…”
Section: Product Development Planning and Documentationsupporting
confidence: 90%
“…For this reason, the team determined that it is essential to include operational leaders in the planning stage so that the empirical knowledge of the staff and the knowledge acquired from the administrative staff complement each other. Doing this delivers improvements on resources, time, money, administration, equipment, and design method, as stated by some authors [35,51].…”
Section: Validation and Improvementmentioning
confidence: 99%
“…The literature most often cites the work of Davenport and Prusak (2000), and De Long and Fahey (2000), which presumed that knowledge is crucial for the organization, defining the relationship between knowledge at the member level and organization levels, developing appropriate social interaction in the organization, and enhancing the willingness of employees to use new knowledge. The literature has highlighted the importance of organizational culture power (Brown, 1998;De Long and Fahey, 2000) to achieve the desired results of knowledge transfer in organizations (Deshpande, 2019;Pascale, 1984). Thus, several studies have reported that employees expect and prefer a stronger organizational culture (De Long & Fahey, 2000; Tobin, 2000); employees believe that strong culture supports their knowledge transfer (Argote & Ingram, 2000;Brown, 1998) and that stronger organizational culture accelerates the transfer of knowledge in organizations (Hansen et al, 1999;Zheng et al, 2010).…”
Section: Organizational Culturementioning
confidence: 99%
“…This was followed by empirical research on the importance of several basic organizational cultures in comprehensive knowledge development, different types of knowledge, and possible solutions for acquiring and achieving individual goals in organizations (Abdelrahman & Papamichail, 2016;Senge, 1995;Zheng et al, 2010). These studies have provided initial evidence about the meaning of organizational culture in knowledge development and established a broader picture of their relations (Deshpande, 2019;Nellen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As found in this study, human aspects (information orientation) did matter in organizational overall performance. Deshpande (2018) had observed that organizational knowledge management did matter in product innovation. In this study, the authors, in the context of organizational technology orientation, noted a similar theme.…”
Section: Implications For Theorymentioning
confidence: 99%